The Image of Collaboration: Mediation and Enervation under Lockdown. (2nd July 2020) - Dare, Eleanor; Antonopoulou, Alexandra
Abstract : Throughout the pandemic and in conditions of 'lockdown', in which the authors could not meet in person, Alexandra Antonopoulou and Eleanor Dare adapted their long-term collaborative writing project, The Phi Books (2008–), to the constraints of pandemic quarantine, in the second lockdown deploying their own chatbot and AI image generator as new collaborators. Given the complexity of such a mediated experience, in which fears around surveillance, corporate control, glitch and signal loss (not to mention illness) have been consistently present, how might we theorize the encounters and complex processes of mediation we experienced online, as writers and academics but also as friends? What, if anything, have we learnt from our collaboration being mediated by one or two corporate platforms? This article elucidates the author's patterns of interpretation and resistance as mediatized and informed by embodied experiences. It also discusses the role of third-party agents, which the authors term 'Coagulagents' (coagulant and agents), serving to destabilize or deterritorialize the familiar presumptions of their work.